ELECTRICAL CONDUCTIVITY OF THE KAOLIN CLAY MINERAL DEPENDING ON THE TEMPERATURE - A. A. Guseinov (Юг России: экология, развитие)
The aim is to study temperature dependence of the electrical conductivity of the kaolin mineral on crystalchemical factors and thermal transformations.Methods. We have applied the method of investigation of geo-electric properties of high-resistivity materials.Results. We gained the results of the study of the temperature dependence of electrical conductivity in the range of 100-1000 °C of the kaolin clay mineral, which is of great scientific and practical importance. We have proved the existence of the general laws of the nature of the change in the electrical conductivity within the temperature range for all the samples studied, due to the existence of associated complexes of elementary defects in the crystal lattice of the mineral, which play an essential role in the kinetic nature in the geosphere of the Earth. Availability of the spectrum values of the activation energy in the extrinsic region characterizes the stepped nature of dehydroxylation and delocalization of protons of hydroxyl groups of non-equivalent positions of power in the crystal lattice of the mineral, which characterizes the formation of fluid regime of sedimentary strata in dehydration.Conclusions. It was found that the behavior of the electrical conductivity is interconnected with the processes caused by the existence of elementary defects associated in complexes in the crystal lattice of the mineral. The range of values of the activation energy of conductivity reflects the process of dehydroxylation and delocalization of protons and hydroxyl groups.